Sustainable Marketing and Corporate Social Responsibility: A Systematic Literature Review on Their Synergy for Long-Term Competitive Advantage - Andi Rafiuddin Syah; Wulan Cahya; Salamah; Hernawati; Hikmah (Management Study Program, Universitas Kristen Indonesia Paulus, 2025)
This article comprehensively analyzes the relationship between sustainable marketing and corporate social responsibility (CSR) as pillars of modern business strategy. Amidst increasing consumer awareness and regulatory pressures, companies are required to integrate economic, environmental, and social aspects in their operations. Sustainable marketing focuses on the development and promotion of environmentally and socially friendly products/services throughout their life cycle, while CSR encompasses ethical and philanthropic initiatives that enhance a company's positive impact on society. This study adopts a systematic literature review method by analyzing secondary data from reputable scientific journals and sustainability reports. The results show that these two concepts are complementary: sustainable marketing is effective in communicating CSR values to stakeholders, while CSR provides an authentic foundation for sustainability claims. Identified benefits include enhanced brand reputation, consumer loyalty, competitive differentiation, and operational efficiency. Despite challenges such as initial costs and measurement complexity, strategic integration of the two is essential for creating shared value and achieving long-term competitive advantage. This article concludes that sustainable marketing and CSR are no longer optional, but rather strategic imperatives for future business success. This study analyzes 40 articles selected from an initial 150 articles through a systematic selection process.